2010
DOI: 10.1177/1553350610376392
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Achalasia: Quantifying the Effect of Symptomatic Disease on Patient Cost Burden, Treatment Time, and Work Productivity

Abstract: Achalasia substantially limits the lifestyle of patients with the disease. It also implies a financial burden of care for patients and leads to decreased work productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Other researches also present good results because from very low initial GIQLI, they present GIQLI post-operatory with superior punctuation, but without reaching equal or higher values to the ones considered as normal, such as the ones from: Ferulano GP, et al [12], Decker G [7] and DeHaan RK, et al [13]. Nonetheless but Nenshi R, et al [14] present in his research a low GIQLI post-operatory result, reflecting a bad HRQL.…”
Section: Resultsmentioning
confidence: 86%
“…Other researches also present good results because from very low initial GIQLI, they present GIQLI post-operatory with superior punctuation, but without reaching equal or higher values to the ones considered as normal, such as the ones from: Ferulano GP, et al [12], Decker G [7] and DeHaan RK, et al [13]. Nonetheless but Nenshi R, et al [14] present in his research a low GIQLI post-operatory result, reflecting a bad HRQL.…”
Section: Resultsmentioning
confidence: 86%
“…12) Moreover, the disease may increase economic and healthcare burdens, and decrease work productivity, which greatly impair patients' QOL. 13) Some studies 13,14) have demonstrated that QOL scores for AC patients were lower than that of general population. Among treatment methods for AC, POEM is a novel therapy, some studies have shown exciting short-term clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…One approach involved the use of a proprietary process to change the crystalline structure to an extended chain (Hyalamer®); it was anticipated that this change would result in a UHMWPE with superior material properties (e.g., yield strength and creep resistance) [108]. However, the clinical experience with this material demonstrated a high failure rate at early stage (<5 years) [109,110]. Another approach was to cross-link the polyethylene.…”
Section: Polyethylenementioning
confidence: 99%